Brittle Bone Brothers: Osteogenesis Imperfecta Conventional Serial Case - Marsha Ruthy Darmawan; Elysanti Dwi Maharani (Biology, Medicine, & Natural Product Chemistry, 2021)
Osteogenesis Imperfecta is a hereditary connective tissue disorder due to COL1A1/2 mutation causing gene defect encoding proteins to metabolize collagen. The skeletal manifestation of OI causing bone incompetence, hence the name brittle bone disease. Here we report three cases of OI type IV in adults. Skeletal conventional X-rays were performed to all patients and all of them has similar results such as bowing deformities of long bones, old union and some non-union fractures with extreme angulation and severe osteoporosis. OI are classified based on skeletal structure, sclera colorization, dentinogenesis, and functional metabolic defect genetically. OI type I and IV can live until adults; also, the same type of OI can be found in siblings. Skeletal conventional X-rays can solely make the diagnosis.